Spinodal decomposition in the Ta-Mo-Al-N films activated by Mo incorporation: Toward enhanced hardness and toughness. Issue 17 (1st December 2018) - Hao, Jun; Zhang, Yidan; Ren, Ping; Zhang, Kan; Chen, Jianhong; Du, Suxuan; Wang, Meijia; Wen, Mao
Abstract: Spinodal decomposition in the transition metal aluminum nitrides, usually triggered by annealing, can enhance hardness via forming coherent nanometer-size domains, but it is still required to activate during fabrication. Herein, Mo was introduced into Ta-Al-N to obtain Ta-Mo-Al-N films by co-sputtering method, which induced two kinds of phase separations, including 15 at% Mo induced presence of stable wurtzite AlN phase and 28 at% Mo activated spinodal decomposition forming coherent fcc-Ta-Al-N and Mo-Al-N nano-domains. It is found that both hardness and toughness would be worsened by presence of hexagonal wurtzite AlN phase at incorporation of 15 at% Mo. On the contrary, once spinodal decomposition took place at 28 at% Mo, achieving the joint targets of enhanced hardness and toughness, together with reduced friction and improved wear-resistance. It may provide a new strategy to activate spinodal decomposition during fabrication by alloying additional elements.